Impact chains for the deep seafloor: assessing pressures footprint under limited knowledge and uncertainty - Matos, Fábio L.; Hilário, Ana; Teixeira, Heliana (Frontiers in Marine Science, 2025)
Pressures on the marine environment threaten biodiversity, ecosystem functions and services. Current marine environmental policies, such as the European Marine Strategy Framework Directive, require the assessment of combined effects and the application of ecosystem-based management approaches to maintain or achieve Good Environmental Status (GES) of marine ecosystems. We mapped the major activities and pressures affecting deep-sea benthic habitats in the mainland component of the Portuguese EEZ to assess their combined effects and support decision-making on management and conservation. Activities related to marine traffic, fisheries, and climate change processes are among the most prevalent in the study area. As a data-poor case study, most of the pressure layers were only partially mapped due to a lack of information or the inadequacy of the available data on activities to derive suitable proxies of pressure intensity. Pressures related to chemical changes, chemicals and other pollutants were the most widespread, while abrasion and damage were the most geographically limited. Endogenic pressures dominate in bathyal benthic habitats and decrease their prevalence with depth, while exogenic pressures are more widespread in the abyss than in the bathyal area. Benthic habitats in the bathyal zone, closer to the 200-meter bathymetric contour, consistently exhibited higher combined effect scores, suggesting higher risk of potential impacts on these ecosystem components. Research directed towards these areas is required to assess the state of these habitats and develop conservation and restoration measures, if necessary, to achieve GES. A continuous support for open-access databases containing high-quality, standardized, and harmonized marine data is crucial for future assessments of the combined effects of human pressures on deep-sea ecosystems.